Três décadas de evoluç\~ao do funcionalismo público no Brasil (1986-2017) - Felix Lopez; Erivelton Guedes (Instituto de Pesquisa Econômica Aplicada (IPEA), 2020)
– This article discusses the Brazilian civil service evolution and patterns of change in each level and branch of government, from 1986 to 2017. Our analysis covers the total personnel, schooling, and distribution by sex, mean and median wages as well as the total government spending on active civil servants. Our main source of data is the Rais database, which includes several improvements from the original source after comparisons with the Receita Federal database. The descriptive panel details important differences between levels of government. We defend the importance of taking into account these differences among varying civil service segments rather than the idea of a generic national civil service, or mistakenly assuming that the federal sector is a reasonable proxy for features in other levels of Brazil's civil service.
Keywords: J45; J48; H70; H83; 330; civil service; bureaucracy; workforce in the public sector; public sector; Brazilian State